Editors’ Introduction - Michael Glanzberg; Jurģis Šķilters (Baltic International Yearbook of Cognition, Logic and Communication, 2015)
Spatial cognition can be considered as a set of foundational and central cognitive abilities that enable a variety of conceptual processes, both non-verbal and verbal. Further, according to recent research, spatial thinking seems to be critical in the development of abstract knowledge and in the processes of abstraction. Although there is a consensus regarding the role and impact of spatial cognition, there are a number of different, divergent, and sometimes even discrepant theoretical and methodological perspectives in the study of spatial cognition.
Keywords: spatial cognition; spatial thinking; baltic yearbook of cognition; cognitive science; linguistics